Research and Application of Embedded Control Software Security Design - DAI Jisheng; WANG Chengjie; LI Yi; CHEN Junbo; LI Cheng (机车电传动)
Security threats faced by embedded control software were analyzed: cloning, reverse engineering, and tampering. The embedded control software security design strategies and security analysis were presented from three aspects of security authentication chip, program encryption and decryption, integrity verification, and security processor. Finally, based on security authentication chip, symmetric and asymmetric encryption algorithm and embedded control softwarre for secure key memory, a security application solution was designed, which could protect the confidentiality, integrity and non-denied of the software. It has great reference value for the embedded controller design.